2016
DOI: 10.1016/j.celrep.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Smurf1 Inhibits Osteoblast Differentiation, Bone Formation, and Glucose Homeostasis through Serine 148

Abstract: Summary The E3 ubiquitin ligase Smurf1 targets the master regulator of osteoblast differentiation Runx2, for degradation yet the function of Smurf1 if any during osteoblast differentiation in vivo is ill-defined. Here we show that Smurf1 prevents osteoblast differentiation by decreasing Runx2 accumulation in osteoblasts. Remarkably, mice harboring a substitution-mutation at serine 148 (S148) in Smurf1 that prevents its phosphorylation by AMPK (Smurf1ki/ki) display an equally severe premature osteoblast differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 30 publications
(45 reference statements)
3
37
0
Order By: Relevance
“…Recent study reports that AMPK phosphorylates Smurf1, the ubiquitin E3-ligase of Runx2, in osteoblast. 50 This phosphorylation blunts Smurf1's ubiquitin E3-ligase activity and thus promotes Runx2 expression in osteoblast. 50 However, we found silencing of Smurf1 could not alter Runx2 expression in VSMC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study reports that AMPK phosphorylates Smurf1, the ubiquitin E3-ligase of Runx2, in osteoblast. 50 This phosphorylation blunts Smurf1's ubiquitin E3-ligase activity and thus promotes Runx2 expression in osteoblast. 50 However, we found silencing of Smurf1 could not alter Runx2 expression in VSMC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…50 This phosphorylation blunts Smurf1's ubiquitin E3-ligase activity and thus promotes Runx2 expression in osteoblast. 50 However, we found silencing of Smurf1 could not alter Runx2 expression in VSMC (data not shown). This might explain why the roles of AMPK in osteoblastic differentiation are opposite in VSMC and osteoblast.…”
Section: Discussionmentioning
confidence: 99%
“…Since bone formation is a process subjected to strict regulation, once the Smad proteins have fulfilled their function, they are ubiquitinated by the HECT‐type ubiquitin ligase Smurf1 (Smad ubiquitination regulatory factor 1), and subsequently degraded by the ubiquitin‐proteasome system . Besides its direct implication in flagging the Smad proteins for destruction, Smurf1 seems to have an additional function leading to the suppression of bone formation, since this protein would prevent osteoblast differentiation by decreasing the accumulation of Runx2 in these cells, and their subsequent differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a pivotal role in colon, pancreatic, and breast cancer tumor progression has been reported for Smurf1 (33). Of note, recent studies have identified Smurf1 as a determinant of bone formation and glucose homeostasis postnatally and have demonstrated its functional role in metabolism (34,35); however, the physiologic roles that Smurf1 plays in the regulation of steroid-induced gonad function have been largely unveiled.…”
mentioning
confidence: 99%